#TITLE_ALTERNATIVE# - Markos Siahaan (NIM 202 98 521), Sardianto
ABSTRACT : This research applied multiphase pseudopressure and pseudotime concepts with appliying semi analytical single phase solution for analysizing of transient-pressure of multiphase oil-gas flow. The pseudopressure and pseudotime concepts involves parameters of multiphase flow properties such as relative permeabilities and reservoir fluids into the two pseudo parameters that could reduce non linearities embedding in the multiphase diffusivity equation. The aim of this study is to examine application of the pseudopressure and pseudotime concepts in analysizing of transient pressure of two phase oil-gas flow with a flow rate constant. This study uses two dimensional, radial reservoir simulation model. That yields bottom hole transient pressure profiles using hypothetical data. In addition, effects of wellbore damage and wellbore storage on the build-up data were also studied. The results indicate that for low absolute permeabilities (50 md) the proposed method can reduce the error up to 10.554 % over the conventional method, and for high permeability (300 md) can reduce the error up to 6.004 % over the conventional method.